Anticancer Applications and Pharmacological Properties of Piperidine and Piperine: A Comprehensive Review on Molecular Mechanisms and Therapeutic Perspectives - Mitra, Sicon; Anand, Uttpal; Jha, Niraj Kumar; Shekhawat, Mahipal S.; Saha, Suchismita Chatterjee; Nongdam, Potshangbam; Rengasamy, Kannan R. R.; Proćków, Jarosław; Dey, Abhijit (Frontiers in Pharmacology, 2022)
Piperine and piperidine are the two major alkaloids extracted from black pepper (Piper nigrum); piperidine is a heterocyclic moiety that has the molecular formula (CH2)5NH. Over the years, many therapeutic properties including anticancer potential of these two compounds have been observed. Piperine has therapeutic potential against cancers such as breast cancer, ovarian cancer, gastric cancer, gliomal cancer, lung cancer, oral squamous, chronic pancreatitis, prostate cancer, rectal cancer, cervical cancer, and leukemia. Whereas, piperidine acts as a potential clinical agent against cancers, such as breast cancer, prostate cancer, colon cancer, lung cancer, and ovarian cancer, when treated alone or in combination with some novel drugs. Several crucial signalling pathways essential for the establishment of cancers such as STAT-3, NF-κB, PI3k/Aκt, JNK/p38-MAPK, TGF-ß/SMAD, Smac/DIABLO, p-IκB etc. are regulated by these two phytochemicals. Both of these phytochemicals lead to inhibition of cell migration and help in cell cycle arrest to inhibit survivability of cancer cells. The current review highlights the pharmaceutical relevance of both piperine and piperidine against different types of cancers.